2012
DOI: 10.1016/j.micinf.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Iron metabolism and the innate immune response to infection

Abstract: Host antimicrobial mechanisms reduce iron availability to pathogens. Iron proteins influencing the innate immune response include hepcidin, lactoferrin, siderocalin, haptoglobin, hemopexin, Nramp1, ferroportin and the transferrin receptor. Numerous global health threats are influenced by iron status and provide examples of our growing understanding of the connections between infection and iron metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
163
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(169 citation statements)
references
References 111 publications
3
163
1
2
Order By: Relevance
“…Although Fe 2+ in phagolysosomes can produce hydroxyl radicals via Fenton reaction, thus potentially killing bacteria, depletion of the iron pool from the phagosome deprives pathogenic bacteria of metal ions that are critical for their survival. Invasive bacteria, such as Legionella pneumophila, Mycobacterium tuberculosis or Salmonella enterica serovar Typhimurium are known to absorb large amounts of iron, while at the same time they are resistant to oxygen radicals (Henard and Vazquez-Torres, 2011;Johnson and Wessling-Resnick, 2012;Kortman et al, 2012;Moalem et al, 2004;Robey and Cianciotto, 2002;Slauch, 2011). Recently, we also showed that L. pneumophila hinders recruitment of the V-H + -ATPase, but not Nramp1, in the Legionella-containing vacuole in a process apparently involving inhibition of phosphatidylinositol-3-phosphate formation.…”
Section: Introductionmentioning
confidence: 89%
“…Although Fe 2+ in phagolysosomes can produce hydroxyl radicals via Fenton reaction, thus potentially killing bacteria, depletion of the iron pool from the phagosome deprives pathogenic bacteria of metal ions that are critical for their survival. Invasive bacteria, such as Legionella pneumophila, Mycobacterium tuberculosis or Salmonella enterica serovar Typhimurium are known to absorb large amounts of iron, while at the same time they are resistant to oxygen radicals (Henard and Vazquez-Torres, 2011;Johnson and Wessling-Resnick, 2012;Kortman et al, 2012;Moalem et al, 2004;Robey and Cianciotto, 2002;Slauch, 2011). Recently, we also showed that L. pneumophila hinders recruitment of the V-H + -ATPase, but not Nramp1, in the Legionella-containing vacuole in a process apparently involving inhibition of phosphatidylinositol-3-phosphate formation.…”
Section: Introductionmentioning
confidence: 89%
“…Individuals with hemochromatosis are susceptible to infections (Vibrio, Yersinia, E. coli), but the overexpression of ferroportin reduces iron in macrophages such that resistance to obligate intracellular pathogens is observed (Mycobacteria, Salmonella, Legionella) (76). In vitro studies show that overexpression of ferroportin disrupts M. tuberculosis growth (77), diminishes growth of Salmonella (78), and reduces HIV replication (79).…”
Section: Roles Of Other Transportersmentioning
confidence: 99%
“…In vitro studies show that overexpression of ferroportin disrupts M. tuberculosis growth (77), diminishes growth of Salmonella (78), and reduces HIV replication (79). Conversely, studies of flatiron mice, which have ferroportin deficiency (70,76,80), demonstrate that loss of its export activity confers greater susceptibility to intracellular pathogens (81). Macrophages from these mice support greater growth of Chlamydophila psittaci, and this effect was lost upon iron chelation (81).…”
Section: Roles Of Other Transportersmentioning
confidence: 99%
“…In mammals, T. brucei lives as a trypomastigote in the bloodstream and tissue fluids [Bitter et al, 1998;Subramanya, 2009;Taylor and Kelly, 2010;Johnson and Wessling-Resnick, 2012]. As an extracellular parasite, it depends on endocytosis to take up nutrients from the host blood [Subramanya, 2009].…”
Section: Use Of Host Transferrin By T Bruceimentioning
confidence: 99%